Evaluating Customer Quality, Satisfaction, And Loyalty In B2B Relations: Insights From PT Telkom Witel Yogyakarta - Lulu Anesa Ardita Putri; Istyakara Muslichah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The main objective of this research is to examine how service quality and brand awareness affect customer satisfaction and loyalty in the business-to-business (B2B) technology services industry. Data was collected through interviews with four respondents with different backgrounds in Yogyakarta and analyzed using the content analysis method. This study shows that service quality has a positive impact on customer satisfaction, customer satisfaction has a positive impact on customer loyalty, and brand awareness has a positive impact on the relationship between service quality and customer satisfaction. The findings will help company managers in the B2B technology services industry to use these insights to improve customer satisfaction through service quality improvement actions.